"Camelots du roi ou rouges": radicalization in early twentieth-century Haitian periodicals. Issue 1 (April 2020) - Stieber, Chelsea
Abstract : This article explores the radicalization of early twentieth-century Haitian periodicals. While the importance of Marxist and radical socialist thought in early twentieth-century Haiti has been the focus of much scholarly attention, the presence of far-right nationalism has yet to receive its due. Maurrassisme, or integral nationalism, is one of the most important French-language ideologies of the early twentieth century – one that scholars often overlook at the expense of fully appreciating its power and reach during the period. Haitian intellectuals' engagement with integral nationalism was part of a wider global engagement with the ideas of Maurras and Action Française in the interwar period. In the case of Haiti, the integral nationalism put forth in Maurrassisme resonated with radicals in the interwar period as they reflected on the failures of the liberal democratic order that resulted from their own revolution in 1804. In fact, Haitians were self-professed adherents of Action Française and its ideology as it related to their own interwar Haitian context. Through a close reading of Haitian periodicals from the period, I argue integral nationalism and fascism were the dominant radical ideologies of the 1930s, more widespread than communism among elite intellectuals and, crucially, with near-unfettered access to the print public sphere.